2021
DOI: 10.3390/ijms22062964
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes in Neoplastic Mast Cells and Potential Impact in Mastocytosis

Abstract: Systemic mastocytosis (SM) is a hematologic neoplasm with abnormal accumulation of mast cells in various organ systems such as the bone marrow, other visceral organs and skin. So far, only little is known about epigenetic changes contributing to the pathogenesis of SM. In the current article, we provide an overview of epigenetic changes that may occur and be relevant to mastocytosis, including mutations in genes involved in epigenetic processes, such as TET2, DNMT3A and ASXL1, and global and gene-specific meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
2
1
4
Order By: Relevance
“…Second, DNMT3A mutations were more common in SM-t(8;21) AML than in KIT pos t(8;21) AML, which favored the opinion that epigenetic changes might play an important role in pathogenesis of mast cell neoplasms. 20 , 21 Last, the incidence of S/A/R mutations in SM-t(8;21) AML was significantly lower than previously reported in KIT D816mut CBF-negative SM-AML and other advanced SM subtypes but close to the frequency in t(8;21) AML, which indicated that the molecular features of patients with SM-AHN may be mainly determined by the AHN component. 22 , 23 , 24 …”
contrasting
confidence: 50%
“…Second, DNMT3A mutations were more common in SM-t(8;21) AML than in KIT pos t(8;21) AML, which favored the opinion that epigenetic changes might play an important role in pathogenesis of mast cell neoplasms. 20 , 21 Last, the incidence of S/A/R mutations in SM-t(8;21) AML was significantly lower than previously reported in KIT D816mut CBF-negative SM-AML and other advanced SM subtypes but close to the frequency in t(8;21) AML, which indicated that the molecular features of patients with SM-AHN may be mainly determined by the AHN component. 22 , 23 , 24 …”
contrasting
confidence: 50%
“…(23) La proteína citoplasmática adaptadora SH3 (3BP2) promueve la señalización de KIT, y su silenciamiento disminuye PI3K, ERK1/2, MITF e induce la apoptosis. (25) MITF, regula la expresión y actividad de KIT (11) y su silenciamiento reduce la viabilidad y ciclo celular, así como la disminución de la degranulación dependiente de IgE en células humanas mastocitarias HMC-1. (26)…”
Section: Resultsunclassified
“…además, se observó la expresión de ciertos microANRs en los exosomas de mastocitos en las muestras de mo en sm: hsa-mir-451, hsa-mir-503, mirplus_27560, mirplus_2843, mirplus_27564, hsa-mir-583, mirplus_1795, mirplus_17890, hsa-mir-663 y hsa-mir-30b. (11)…”
Section: Mitf Y Microarnunclassified
“…Although the specific role of each individual epigenetic alteration detected in SM remains unknown [127][128][129][130], recurrent mutations in genes involved in epigenetic modifications of DNA (i.e., ASXL1, CILK1, DNMT3A, EZH2, IDH1, IDH2, KAT6B, NPM1, SETBP1 and TET2 genes) have been recurrently identified (Table 2, Tables S1 and S2); among these, mutations involving the ASXL1, DNMT3A, EZH2 and TET2 genes are the most commonly reported ones (Table 4).…”
Section: Mutations In Genes Involved In Epigenetic Regulatory Mechanismsmentioning
confidence: 99%